Obliteration of phosphorus deficiency in plants by microbial interceded approach - Dipta, B.; Bhardwaj, S.; Kaushal, M.; Kirti, S.; Sharma, R. (Springer, 2019)
Phosphorus plays an indispensable part in keeping up soil richness and securing global sustenance production, however, its chief proportions remain interlocked in various insoluble forms of Ca, Fe and Al ion precipitates that cannot be taken by the plants proficiently. This prompts to an indiscriminate application of phosphatic chemical fertilizers to the crop field which has led to substantial pollution of soil, air, water and deleterious effects on soil health due to leaching and run-off of phosphorus into soil and water table. Microorganisms such as bacteria, fungi, actinobacteria, and cyanobacteria play a crucial role in mobilizing inorganic and organic P in the soil and simultaneously increases P uptake by the plant. In the present review, endeavors have been made to emphasize on the occurrence, mechanism, the role of phosphate solubilizing bacteria in solubilization of fixed phosphorus and genetics of phosphate solubilizing microorganisms.